CONNECTION BETWEEN THE CME VELOCITIES AND DECAMETER RADIO BURSTS PARAMETERS FROM URAN-4 OBSERVATIONS - Galanin, V. V.; Isaeva, E. A.; Kravetz, R. O. (Одеські астрономічні публікації, 2016)
The paper reports the results of the research of connection between the coronal mass ejections (CME) with the IV type continual decameter bursts parameters. As the parameters characterizing the CME velocity, we used the integrated flux of the radio bursts and background intensity on 20 and 25 MHz frequencies. The analysis demonstrated that the connection between the CME velocity and IV type bursts increases, if we take into account the intensity of the radio bursts and background on two polarizations at a given frequency. In this case, the correlation coefficient is ≈ 0.75.